1947
DOI: 10.1002/jcp.1030290103
|View full text |Cite
|
Sign up to set email alerts
|

The action of various cations on muscle protoplasm

Abstract: Zoo-logioal I a b o r a t o r y , University of Pennsylvania, PhiladelphiaThere are 2 ways to study the colloidal behavior of muscle protoplasm. One way is to isolate individual proteins of the muscle. The colloidal behavior of such proteins can then be followed exactly in test tubes or other suitable containers. In recent years, biochemists have learned to make relatively pure preparations of muscle proteins and the physical or colloidal properties of these proteins have been carefully noted by many investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1

Year Published

1955
1955
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(112 citation statements)
references
References 11 publications
6
105
1
Order By: Relevance
“…Calcium was early shown to be the only physiological ion that causes shortening of muscle fibers when injected at low concentrations (11). This is consistent with recent evidence that protoplasmic calcium is largely in bound form (3,9,14).…”
Section: Discussionsupporting
confidence: 81%
“…Calcium was early shown to be the only physiological ion that causes shortening of muscle fibers when injected at low concentrations (11). This is consistent with recent evidence that protoplasmic calcium is largely in bound form (3,9,14).…”
Section: Discussionsupporting
confidence: 81%
“…proved effective. These findings cemented prior work by Heilbrunn and Wiercinski (1947) who had used a cruder, pressure injection technique in cut, unrestrained fibre segments. Rolf's pilot study was not followed up or reported in detailpartly because of limited experimental time on the critical interference microscope.…”
supporting
confidence: 67%
“…Effects of the micro-injection of various substances on the contractile mechanism of Maia muscle fibres Calcium and barium chlorides have been reported previously to cause contraction when introduced into frog muscle fibres by micro-injection or micro-electrophoresis, whereas magnesium, sodium and potassium chlorides have been reported to be without effect (Heilbrunn & Wiercinski, 1947;Niedergerke, 1955). The effects of the micro-injection of solutions of these substances were therefore among the first experiments tried.…”
Section: Resultsmentioning
confidence: 99%